Synthesis and evaluation of a large library of nitroxoline derivatives as pancreatic cancer antiproliferative agents. (1st January 2020) - Veschi, Serena; Carradori, Simone; De Lellis, Laura; Florio, Rosalba; Brocco, Davide; Secci, Daniela; Guglielmi, Paolo; Spano, Mattia; Sobolev, Anatoly P.; Cama, Alessandro
Abstract: Pancreatic cancer (PC) is one of the deadliest carcinomas and in most cases, which are diagnosed with locally advanced or metastatic disease, current therapeutic options are highly unsatisfactory. Based on the anti-proliferative effects shown by nitroxoline, an old urinary antibacterial agent, we explored a large library of newly synthesised derivatives to unravel the importance of the OH moiety and pyridine ring of the parent compound. The new derivatives showed a valuable anti-proliferative effect and some displayed a greater effect as compared to nitroxoline against three pancreatic cancer cell lines with different genetic profiles. In particular, in silico pharmacokinetic data, clonogenicity assays and selectivity indexes of the most promising compounds showed several advantages for such derivatives, as compared to nitroxoline. Moreover, some of these novel compounds had stronger effects on cell viability and/or clonogenic capacity in PC cells as compared to erlotinib, a targeted agent approved for PC treatment.